A deletion in the α subunit locks platelet integrin αIIbβ3 into a high affinity state - Peter, Karlheinz; Bode, Christoph (Blood coagulation & fibrinolysis, 1996)
The integrin αIIbβ3 (GPIIb/IIIa) mediates platelet aggregation by a change in affinity for the ligand fibrinogen. The amino acids 991-995 (GFFKR) at the NH2-terminus of the cytoplasmic domain are highly conserved in all known integrin α subunits. We postulated that the GFFKR-region is important for the inside-out signal transduction and has an influence on the affinity state of integrals. To test this hypothesis, a mutant with a deletion in the GFFKR region was designed. The DNA-constructs were constructed by PCR, sequenced, cotransfected with the β3 subunit into CHO cells and cell surface expression was proven with immunoprecipitation and flow cytometry. The GFFKR-deletion mutant demonstrated a high affinity binding of the mAb PAC-1 and I125-labeled fibrinogen. The metabolic inhibitors 2-deoxyglucose and NaN3 did not change the affinity state of the deleted receptor. Neither did the truncation of the cytoplasmic domain of the β3 subunit. Additionally, expression of the deleted integrin in the erythropoetic cell line K562 revealed a high affinity state. A deletion of the GFFKR-region in the cytoplasmic domain of the α subunit locks integrin αIIbβ3 in a high affinity state. This is an intrinsic property of the deleted receptor since there is no energy dependence and no cell type specifity. Thus, the GFFKR-region is involved in inside-out signaling in αIIbβ3Furthermore, cell lines expressing this activated αIIbβ3 integrin may be used as models for activated platelets.
Im Titel sind "IIb" und "3" tiefgestellt
Gesehen am 25.04.2024